Building bridges instead of putting up walls: connecting the "teams" to improve soccer players' support - Silva, J. R.; Buchheit, M.; Hader, K.; Sarmento, H.; Afonso, J. (Sports Medicine, 2023)
The increase in the economic value of soccer occurred in parallel with an increase in competing demands. Therefore, clubs and federations evolved to greater specialization (e.g., state-of-the-art facilities and high-profile expertise staff) to support players` performance and health. Currently, player preparation is far from exclusively club or national team centered, and the lack of control in each player`s environment can be more prevalent than expected. For example, an elite group of professional players faces disruptions in the season club-oriented planification due to involvement in national teams. Moreover, as elite players` financial resources grow, it is common for them to employ specialized personal staff (e.g., strength and conditioning, nutritionist, and sports psychologist) to assist in their preparation, resulting in complex three-fold relationships (i.e., club, player`s staff, national team). Although efforts have been made to improve communication with and transition from the club to the national team supervision, this new reality (club-players` staff) may generate serious compound role-related problems and difficulties in monitoring load and training adaptation and having a unified message. Therefore, efforts must be implemented to ensure a more informed management of the players` performance environment, where the existence and impact of these various personal staff are considered to avoid a long-term non-zero sum for all intervening parties. If left unchecked, current professional thinking may collide or overlap, potentially triggering conflict escalation and impairing athletic performance or health, especially if effective communication routes are not adequately established. Moreover, diluted personal responsibility regarding performance may ensue, resulting in decreased productivity from all involved, which may cause more harm than benefits for the player`s overall health and performance. This emerging reality calls for developing a joint working framework (i.e., between the player`s personalized support team and the clubs` team) and better managing of a player-centered process.